The importance of music in child development (Research, Society and Development, 2022)
Music is very rich in numerous aspects for moving and awakening the human being to experience knowledge, expression and socialization in learning. In Early Childhood Education, music can favor discoveries that facilitate the development and training process. In this perspective, the present study aims to: reflect on the contributions of music in child development. Therefore, the following specific objectives are outlined: Identify the evolution of the profile of music in the history of the human being and list the main contributions of music in human development, specifically for the child. The bibliographic research is anchored in the studies of some theorists such as RCNEI, Freire, Brito, Alencar, Ferreira among others. It is hoped that these reflections serve as a motivation for other researchers to expand these discussions and/or bring new aspects about what is relevant and productive in pedagogical methodologies in early childhood education.